ANALYSIS OF INCREASING EFFICIENCY METHODS FOR ELECTROSLAG PROCESS BY MEANS OF CHANGING THE HEATING CONDITIONS OF THE CONSUMED ELECTRODE - Bilonik , Igor; Popov , Sergiy; Shumykin , Sergiy; Davidchenco , Stanislav; Bilonik , Dmitry (Scientific Journal "Metallurgy", 2020)
One of the problems of electroslag remelting (ESR) is a high energy consumption and the restriction of admissible speeds of the weld metal. This is due to the specifics of the technologies for melting, casting, fusing and welding. A characteristic feature of the technology is the combination of the processes of melting, refining and solidification of metals in a receptacle (a water-cooled mold). Course structure and homogeneity of cast steel, the degree of contamination of non-metallic inclusions, as well as sulphur, phosphorus and gases depend on the thermal conditions of melting of consumable electrode. Various methods and devices to increase the temperature in the zone of the consumable electrode: coaxial introduction into the slag bath nonconsumable electrode; applying a magnetic field are studied. Most effective, in this respect, two diagrams superimposed on the slag bath of a transverse magnetic field, and superimposed on the liquid metal bath of reverse magnetic fields. In the first case, increases the intensity of metal processing liquid slag, while maintaining the crystallization conditions. In a second embodiment, the liquid metal receives the reverse rotational movement, in which the crushing of the primary dendritic axes and small equiaxed grains are formed. Significant changes in the melting performance and mechanical properties of the metal. It is shown that for steel 14Х2Н3МА you can increase the speed of melting of the ingot to between 6.7 to 29.5%, and the mechanical properties increase up to 4.8%.. casting of steel EI 481 mechanical properties, increase on average by (5- 10) %' and long-term strength and ductility increase to 1.15 to 1'25 and 2.2-2'5 times, respectively. However, the application of the method is limited by casting, having a simple form of bodies of revolution. Also the technology of smelting with a jet of gas is considered at the melting end of the consumable electrode. The observed increase in melting performance, and moving centers kapleobrazovanie to the periphery of the end face of the electrode. . Theoretical studies in NMA shows that the application of additional heating source consumable electrode provides increased technical and economic indicators of the process. The possibility of cost reduction of electricity by 18-20% and also improve performance of the process of the ESR on 10 %.